ANALISIS DIVERSIFIKASI PRODUK OLAHAN SALAK WEDI MENGUNAKAN METODE QUALITY FUNCTION DEPLOYMENT(QFD) DAN METODE ANALYTICAL HIERARCHY PROCESS (AHP): ANALISIS DIVERSIFIKASI PRODUK OLAHAN SALAK WEDI MENGUNAKAN METODE QUALITY FUNCTION DEPLOYMENT(QFD) DAN METODE ANALYTICAL HIERARCHY PROCESS (AHP) - khakim, moh yusuf dawud; Darsan , Darsan (Viabel : Jurnal Ilmiah Ilmu-Ilmu Pertanian, 2020)
The result of this research is the objective of consumer satisfaction, almost all the attributes of Processed Coffee Beans Salak Wedi have outperformed its competitors, except for the attributes of the product packaging size which is compact and proportional, this will increase the value of sales and technical points. response as a long-term strategy, so that the value of priority contributions is increased and taken into account. Meanwhile, the value of the priority contribution of customer needs is the answer to the technical response to improvements that must be made by the Salak Wedi coffee bean home industry. There are 5 priority actions in accordance with the recommendations from the priority data processing of contribution value. The results of AHP analysis show the conclusion that the most appropriate alternative strategy for the home industry of Salak Wedi bean coffee is a product differentiation strategy with a focus on the company's competitive advantage. Attention to Marketing Costs still needs to be done for the purpose of process efficiency by removing waste and potential waste from the production process. Of course, a focus on eliminating waste will have a positive impact on improving product quality, functionality and reliability. However, Marketing Cost in this context is not part of a competitive strategy but is an improvement process for companies to increase their competitive advantage in facing current market competition.